Genetic diversity assessment among Corema album (L.) D. Don (Ericaceae) genotypes based on ISSR markers and agro-morphological traits - Jacinto, João; Oliveira, Pedro Brás; Valdiviesso, Teresa; Capelo, Jorge; Arsénio, Pedro; Nóbrega, Filomena (Springer, 2020)
Research Article Corema album (L.) D. Don is the only species of the genus Corema growing naturally on sand dunes throughout the Atlantic coast of the Iberian Peninsula, noted for the white coloured berries and nutritional value. The lack of information on genetic studies of the species is one of the most limitations for the establishment of this species as a new culture. Thus, this study focuses on the assessment of the genetic diversity based on inter-simple sequence repeats (ISSR) molecular markers and morphological traits. Seventy-one female plants, from four different sampled sites, were evaluated using six ISSR loci and eight morphological traits. Fifty polymorphic loci were detected. The dendrogram based on the UPGMA method and the principal coordinate analysis classified the 71 C. album genotypes into distinct clusters. The analyses revealed that accessions from the same geographical area were generally, but not entirely, clustered into the same group. Analysis of molecular variance was higher among populations, than within populations. The analysis of morphological traits revealed that there is no distinct separation among the C. album genotypes grown in different geographic areas. To our knowledge, this is the first study on the assessment of the genetic diversity in this species info:eu-repo/semantics/publishedVersion